FRI0052 Large Joint Involvement in Asian Rheumatoid Arthritis Patients: A Longitudinal Study of Treatment Outcomes Using Power Doppler as a Bedside Monitoring Tool in 101 Patients. (9th June 2015) - Cheung, P.; Lahiri, M.; Teng, G.G.; Lim, A.; Gossec, L.; March, L.
Abstract : Background: Although rheumatoid arthritis (RA) classically involves small joints, large joints can also be affected. Clinical experience indicates this involvement may be frequent particularly in the Asian population. The impact of this large joint involvement has been little assessed. Power Doppler ultrasound (PDUS) can assist as a bedside tool for disease assessment. Objectives: Evaluate the clinical outcomes of patients with active large joint synovitis, using PDUS as a bedside tool for disease activity assessment. Methods: Secondary analysis of a randomized controlled trial of patient education [1]. Consecutive established RA patients were followed over 6 months. Clinical synovitis, followed by PDUS synovitis was assessed on 28 joints (2 shoulders, 2 elbows, 2 wrists, 10MCP, 10PIP, 2 knees) of each patient. PDUS was graded semiquantitatively (0-3); active synovitis defined as ≥ Grade 1. Treatment adjustments were made every 3 months, at clinician's discretion, based on clinical and PDUS findings [1]. For the present post-hoc analysis, patients with PDUS large joint synovitis (at least 1 joint among shoulders, elbows or knees) were compared to those without, for: (i) frequency of large joint involvement, (ii) proportion with treatment escalated (increase in dose/addition of disease modifying anti-rheumatic drugs, or increase/addition in prednisolone), (iii) level of disease activity (disease activity score 28, DAS28), and patient reported outcomes (rheumatoid arthritis impact of disease (RAID) and physical function (SF-12PCS)) at baseline and 6 months. Results: 101 patients with median (IQR) age of 54.3 (48.4, 62.8) years, disease duration of 5.3 (2.2, 9.4) years and median DAS28 of 3.2 (2.5, 4.2) were studied. 72% were Chinese. PDUS detected 44% of patients with large joint disease at baseline (shoulders 21%, elbows 20% and knees 6%), missed by 50% on clinical assessment alone. Patients with large joint PDUS disease had higher DAS28: median 3.8 (3.0, 5.0) vs. 2.8 (2.2, 3.4), p<0.001; higher RAID: median 3.2 (1.4, 5.2) vs. 1.7 (0.5, 2.6), p<0.001; and poorer SF12PCS: 39 (33, 50) vs. 45 (37, 52), p=0.034 than those without large joint disease. Over 6 months, more patients with large joint disease had treatment escalated compared those without (75% vs. 51%, p=0.015). Only 16% of patients still had PDUS large joint disease after 6 months, with less missed by clinical assessment alone (37%). The median DAS28 of patients with initial large joint disease decreased to 3.4 (2.6, 4.6): thus a median DAS28 decrease of 0.2 (-0.1;0.9) in patients with large joint disease vs. 0 (-0.5;0.6) in those without, p=0.047. Impact of disease improved, with median RAID reduction of 1.0 (-0.5;2.1) vs. 0 (-1.0;0.9), p=0.011, but not physical function (SF-12PCS), (p=0.39). By 6 months, differences in impact of disease between patients with baseline large joint disease and those without, were no longer observed (RAID, p=0.11). Conclusions: Bedside PDUS enables more frequent detection of large joint disease which is linked to worse outcomes in patients with established RA. Combining this with routine joint assessment allows appropriate treatment escalation; potentially improving impact of disease, but not physical function. References: Cheung et al. Rheumatology (Oxford) 2014 Dec 3. Disclosure of Interest: None declared